Case Report of Alagille Syndrome in a Pregnant Patient: A Arrative Review of the Diagnosis and Treatment - Rojas-Urrea, Alejandro; Arias-Mariño, Daniela; Landines-Peña, Fernanda E.; Niño-Patarroyo, Brumel Armando; García-Agudelo, Lorena (Gynecology Obstetrics & Reproductive Medicine, 2025)
Alagille syndrome is a genetic disorder with an autosomal dominant hereditary pattern. Clinical manifestations include craniofacial, ocular, cardiac, hepatic, renal, vascular, and skeletal abnormalities with varying phenotypic penetrance; therefore, treatment would be targeted to the affected organs. A successful pregnancy in this pathology is uncommon and depends on the maternal features, particularly those that involve the cardiovascular and hepatobiliary systems. The objective of the manuscript is to present the case of a 24-year-old pregnant woman with a diagnosis of Alagille syndrome, her therapeutic challenge, and associated conditions.